Peningkatan Kemampuan Membaca Al-Qur’an melalui Penerapan Metode Ummi Bagi Santri Pondok Pesantren Al-Waridin Kabupaten Madiun - Prayitno, Mustofa Aji; Albab, Muhammad Ulil; Fadly, Wirawan (LPPM Universitas Flores, 2023)
One method that can be used in the education of reading and writing the Qur'an is the Ummi Method. The Ummi method is a method of reading the Qur'an with tartil. Although it is classified as a new method, it has been used by more than 1000 institutions in 24 provinces in Indonesia in 2018. The objectives to be achieved in this community service research are: 1) Introducing the Ummi method to the students of the Al-Waridin Islamic boarding school; 2) Improve the ability to read the Qur'an properly and correctly according to the law of reading (tajwid) and makhorijul letters for students of Al-Waridin Islamic boarding school; 3) Improve the ability to read the Koran with mujawas (tone). The method used is the ABCD (Asset Based Community Driven) method which focuses on improving the ability to read the Qur'an through the application of the Ummi method for the students of the al-Waridin Islamic boarding school. The ABCD method is considered appropriate to be applied because it is asset-based which is in line with the potential possessed by Islamic boarding schools in particular and Pagotan Village in general. The ABCD method has six stages, namely 1) discovery, 2) dream, 3) design, 4) define, 5) destiny, and 6) reflection. The results of the community service research show that the training to read the Qur'an using the ummi method for students at the al-Waridin Islamic boarding school can be declared successful. Participants who previously did not know the makhorijul letters, now have begun to understand and are able to apply the correct pronunciation of makhorijul letters, participants who previously did not know the Ummi method became aware of the methods and styles used in the Ummi method. It is hoped that through training to improve the ability to read the Qur'an through the application of the Ummi method for the students of the Al-Waridin Islamic Boarding School, it can increase the interest of the Al-Waridin Islamic boarding school students to explore the sciences in reading and writing the Qur'an and can increase students' interest in learning Arabic properly and correctly.